The Effect of Brand Value, Brand Awareness, Brand Loyalty on Brand Equity in Sharia Banking Industry - Jannah, Kamalina Din; Triyani, Dian; Prapti, Rr Lulus (Universitas Semarang, 2022)
Brand fairness is one of the center elements of marketing, all marketing strategies are basically the goal of building a solid brand. Brands have solid equity to succeed in gaining unswerving consumer advertising and economic benefits. When earlier than finding out to turn out to be a purchaser or client, of course, consumers are inflated through many stuff that inspire them. Therefore it is very meaningful to analyze the key factors that motivate the use of brand equity and customer service at that time to look for correlations and obtain suitable conclusions. The object that is being studied is the customer of Islamic banking.The purpose of this analysis is to identify the impact of brand value, Brand Awareness, Brand Loyality on Brand Equity at Bank Muamalat in Semarang. The studies technique used on this studies is thru a survey. Information is analyzed quantitatively and uses a causative studies design. The tactic of taking illustrations used in this research is to use Non-Probability Sampling with purposive sampling method. All of the illustrative facts received via way of means of dispensing questionnaires is 100 respondents and might be processed the use of the SPSS 24 software feature.